Blockchain-Enabled Secure and Decentralized Resource Management for Open Radio Access Network Cellular Networks - Dheyaa Marjan Hussein Almuntifeky; Basim K. J. Al-shammari (Wasit Journal of Engineering Sciences, 2024)
The rapid growth of Open Radio Access Networks (Open RAN) necessitates innovative resource management systems to address security and decentralization challenges. This study proposes the use of blockchain technology for enhancing the security, privacy, and decentralized decision-making in Open RAN cellular networks. The research focuses on secure communication between O-DU (Distributed Units) and O-CU (Centralized Units) using blockchain technology, along with smart contracts for O-DU to O-CU mapping, thereby ensuring data integrity and authenticity in resource management transactions. By leveraging a blockchain network and consensus methods, this study aims to validate resource management transactions securely and transparently. Smart contracts enforce resource management rules and adapt O-DU to O-CU mapping based on real-time network conditions. The experimental framework simulates an Open RAN environment with multiple O-DUs and O-CUs under dynamic network conditions and traffic demands, rigorously testing blockchain's security in O-DU to O-CU transactions. This study demonstrates that the proposed solution can improve transaction security, trust, transparency, smart contract automation, reduce resource allocation delay, and increase flexibility to dynamic network circumstances. The findings contribute to the ongoing efforts in enhancing the efficiency, security, and flexibility of 5G and beyond.